Purification of manufacturing wastewater from oil products in machinery construction and metallurgy - O. A. Belyj; A. I. Ratjko; A. S. Panasjugin; G. V. Bondareva; N. V. Kitikova; A. E. Tsvetkov (Литьë и металлургия, 2000)
It is shown that mineral sorbents of high activity on the basis of aluminosilicates suitable for water purification from oil products are manufactured by thermal activation of clay minerals containing organic matters.